Small talk, big impact – The influence of casual collegial advice on purchasing negotiations. Issue 5 (December 2019) - Lu, Jiachun; Kaufmann, Lutz; Carter, Craig R.
Abstract: The concept of behavioral supply management has attracted substantial research attention since its introduction about a decade ago. Nevertheless, it is still in a developmental stage, and the supply management field represents a unique and fertile ground for more behavioral research. In this paper, we demonstrate the uncharted potential of behavioral supply management with a special focus on casual advice-giving, which is broadly present in everyday organizational interactions. The study differentiates among three collegial advice types for buyers – to be honest, bluff, or lie – and investigates its influence on subsequent buyer–supplier negotiations. Scenario-based experiments show that advisees are prone to heed advice to be honest and to bluff, but not heed advice to lie in supplier negotiations. Further, we found that, regardless of the advice content, advisees seem to be indifferent to whether the advice is solicited or unsolicited and the advice-giver's job function. Finding that even small talk can have a big impact, we conclude with a call for more behaviorally-focused empirical research and a broader agenda for behavioral supply management. Highlights: Casually provided collegial advice impacts buyers' subsequent negotiation behavior. Buyers are prone to heed advice to be honest and to bluff, but not to lie. Advisees seem indifferent to the advice being solicited or unsolicited in regard to their intention to follow the advice. Advisees seem indifferent to the advice-giver's job function in regard to their intention to follow the advice. A roadmap and agenda of future behavioral supply management research is provided.